Industrial training report: Istana Kehakiman / Nur Akilah Che Abdullah - Che Abdullah, Nur Akilah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
During my two-month internship at Pejabat Ketua Pendaftar Mahkamah Persekutuan Malaysia (PKPMP), the student learned the importance of record management in guaranteeing the organization's efficiency and correctness. The student discovered how digital record-keeping solutions simplify operations, improve accessibility, and assist maintain data integrity. Throughout the training, the student worked with numerous departments, which allowed me to observe how teamwork and communication are essential for managing big numbers of documents. The student also learned about the complexities of record management and the significance of regular audits. This experience enhanced my understanding of record management processes and provided hands-on learning in a professional context.